COMAMMOX - a new pathway in the nitrogen cycle in wastewater treatment plants - Sobotka D; Kowal P; Zubrowska-Sudoł M; Mąkinia J (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2018)
The complete nitrification process, i.e. complete oxidation of ammonia to nitrate (COMAMMOX), by only one microorganism was experimentally confirmed only two years ago. That discovery is now considered a real breakthrough in the nitrogen cycle in the environment and it opens new questions regarding the nitrogen metabolism by microorganisms. Moreover, it also brings opportunities to revise the approach to nitrogen management in wastewater treatment systems employing the novel nitrogen removal processes, such as deammonification or shortened nitrification-denitrification. The comammox bacteria may significantly disturb nitrite production in partial nitrification, which is the critical step for the successful operation of both novel processes. The crucial role in identification of "comammox" bacteria is attributed to the latest, advanced molecular techniques (metagenomics and metatranscryptomics).